The Potential of Probiotics from West Sumatra, Indonesia on Low-Density Lipoprotein and Interleukin-6 Levels with Dyslipidemia - Ridwan, Rhinie Uphita; Putranto, Wachid; Nuhriwangsa, Adi Magna Patriadi (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2024)
Dyslipidemia is a lipid metabolism disorder characterized by abnormal elevations or reductions in one or more lipid fractions within the plasma. This condition is a critical component of both metabolic syndrome and cardiovascular disease (CVD). This study aims to see the potential of curd administration on Low-Density Lipoprotein (LDL) and Interleukin-6 (IL-6) levels in dyslipidemia patients. This study is an experimental study with a pre-post test control group design consisting of a control group and a treatment group totaling 42 people taken randomly at the DR Drs M Hatta Bukittinggi Brain Hospital in June and July 2024. In the three groups, LDL and IL-6 examinations were carried out and measured before and after curd for 14 days. Treatment group 1 was given curd as much as 150 grams, treatment group 2 was given curd as much as 200 grams, given 1x a day, and the control group was not given curd. Data analysis was performed using the Wilcoxon statistical test and paired t-test. Results: There was no significant difference in LDL (p=0.360) and IL-6 (p=0.932) levels after giving curd for 14 days. However, there was a decrease in LDL and IL-6 levels after giving curd for 14 days. Conclusion: The results showed that giving curd for 14 days in the treatment group 1 (150gram) and treatment 2 (200gram) can reduce LDL and IL-6 levels. Consuming probiotics for 14 days can reduce LDL and IL-6 levels.